Access to versus Use of Loans: What are the True Determinants of Access? - Christa Hainz; Tatjana Nabokin (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
Access to finance is a prerequisite for economic development. Existing studies measure access by the use of finance. We develop a direct measurement for access to finance from the Business Environment and Enterprise Performance Survey 2005 data. We determine whether a firm without a loan does not need one or is indeed credit-constrained. The determinants of access estimated in a Heckman selection model are compared with those of use. Our results show that firm age and sector effects do not influence access although they are significant in the use regression. The reasons are differences in demand.
Keywords: G21; O16; 330; Access to Finance; Use of Finance